2018
DOI: 10.1186/s12893-018-0347-x
|View full text |Cite
|
Sign up to set email alerts
|

Pylorus drainage procedures in thoracoabdominal esophagectomy – a single-center experience and review of the literature

Abstract: BackgroundPylorotomy and pyloroplasty in thoracoabdominal esophagectomy are routinely performed in many high-volume centers to prevent delayed gastric emptying (DGE) due to truncal vagotomy. Currently, controversy remains regarding the need for these practices. The present study aimed to determine the value and role of pyloric drainage procedures in esophagectomy with gastric replacement.MethodsA retrospective review of prospectively collected data was performed for all consecutive patients who underwent thora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…Pyloric interventions have been thought of as the major form of prophylaxis against DGE. There are 5 pyloric management strategies at the time of esophagectomy: no intervention [52,53], botulinum toxin injection [37], finger fracture [15], pyloroplasty [54], and pyloromyotomy [7,39]. Each method has its advantages and disadvantages, so we cannot say with certainty which one is the best.…”
Section: Pyloric Drainage Proceduresmentioning
confidence: 99%
“…Pyloric interventions have been thought of as the major form of prophylaxis against DGE. There are 5 pyloric management strategies at the time of esophagectomy: no intervention [52,53], botulinum toxin injection [37], finger fracture [15], pyloroplasty [54], and pyloromyotomy [7,39]. Each method has its advantages and disadvantages, so we cannot say with certainty which one is the best.…”
Section: Pyloric Drainage Proceduresmentioning
confidence: 99%
“…Although there was no statistically significant difference in the emptying rate or gastric drainage, the authors recommended BT because it is simple, effective, and complication-free. In 2018, Fritz et al [ 40 ] published a retrospective study without a control group. Ivor Lewis operations were performed using a gastric tube and the authors concluded that PD may not be warranted because the complication rate did not differ significantly from that of historical PD studies.…”
Section: Comparative Studies and Expert Reviewsmentioning
confidence: 99%
“…Commonly, the incidence of clinically relevant DGCE is considered to be in the range of 10-20% (16)(17)(18). Manifestation of symptoms of DGCE has however been reported to occur in over 50% of patients after esophagectomy (9,(19)(20)(21).…”
Section: Epidemiology Of Dgcementioning
confidence: 99%